Recordações à luz da TV: construções televisivas de memória-indivíduo-sentimento - Damasceno, Alex Ferreira (Universidade do Vale do Rio dos Sinos, 2011)
This study is a communication interface with Philosophy, which articulates two themes: television and memory. At first, we work with theoretical perspectives in the communication field, especially concepts of mediatization, “audiovisualidades” and “ethicidades televisivas”. On the other hand, we research information about memory in the philosophical thoughts of Henri Bergson, Paul Ricoeur and Sören Kierkegaard. The theoretical tensions allowed the quality construction of the object (which was named Televisual Remembrance), whose monitoring is guided primarily by three points: 1) the TV times when memories of the multiple natural individuals television are produced, 2) the individual memories of television – the intrinsic, private and identity pasts; 3) a sentimental reflection of the past, that each individual do by themselves. Aiming to appropriate this object in its heterogeneity and processuality, we articulated the intuitive method to the research from Henri Bergson. In the first stage of method, we mapped the lines of differentiation. For this purpose, we devised three categories of moving boundaries, inspired by the Constellation metaphor of Walter Benjamin: 1) Life reports, when the TV becomes a way of self-enunciation, with oral narratives about the past; 2) Testimonials of television facts, which also contains oral speeches, but aiming at the reconstruction of public events; 3) Mental images, when the TV constructs memory-images. After all, in the second stage of Intuition, the divergent lines were converged to a virtual point, becoming the object in a concept. The Televisual Remembrance is defined as a practice of construction of individual memories, which, through the use of some discursive elements, remains under the television control, and it is used to create actions that perpetuate its power.
Keywords: Televisão; Memória; Memória individual; Recordação televisual; Television; Memory; Individual memory; Televisual remembrance; ACCNPQ::Ciências Sociais Aplicadas::Comunicação